Sistem Informasi Manajemen Berita Dan Iklan RRI Berbasis Website - Hariati Husain; Citra Y Gobel (JSAI (Journal Scientific and Applied Informatics), 2022)
Radio Republik Indonesia is a radio that has a strategic position, because in reality RRI is still the only national network and is able to reach almost all parts of Indonesia. RRI Gorontalo currently still needs a system in news and advertising management. Currently, it still uses conventional services where the process of broadcasting news and advertising services still requires a fairly complicated and time-consuming flow for reporters and advertising services still have to be submitted directly by visiting the RRI Gorontalo office. The purpose of this study is to design a news management information system as a result of reporter coverage for managing news that goes to the editor and advertising services through the website. A proposed system is expected to be able to provide access rights to all related parties, so that reporters can add, edit, and delete news directly. While advertising can be submitted via the web without the need to come to the RRI office. The results of the study concluded that a website-based news and advertising Management Information System was built using the PHP programming language and MySQL database with 3 different user accesses, namely the administrator user as the master data manager, the reporter user and the RRI client as the user client on the system. This website-based information system is expected to help RRI Gorontalo in the process of submitting news services from reporters and receiving advertisements from clients, so that they can run more effectively and efficiently. Based on the results of system testing on the whitebox method, it is concluded that the calculation of V(G) = 2 and Cyclometic Complexity (CC) = 2, so that it can be concluded that the logic flow for the Member Input module carried out by the admin is effective and efficient